Penilaian Tingkat Kematangan Tata Kelola Sistem Informasi Sumber Daya Manusia dengan Cobit Domain Plan and Organize dan Acquire and Implement - Abdul Rahman Kadafi; Eko Setia Budi; Raden Bagus Dimas Putra (Universitas Budi Darma, 2021)
Information technology is currently a technology that is widely adopted by almost all organizations and is believed to be able to help increase the efficiency of ongoing processes, including in educational institutions. IT Governance offers various solutions, innovations, and changes to the company's business, however, the application of information technology must be in accordance with the company's business objectives. The key to entering the world of global business is a qualification that includes skills, knowledge and experience combined with international certification for global recognition. The application of information technology must be tailored to the needs of the institution in order to achieve institutional goals. This research was conducted to conduct an assessment and evaluation of the governance of the Human Resources Information System (HRIS) at the Nurul Fikri Integrated Islamic School, Depok. Knowing this condition will make it easier to take action to improve HRIS governance, use the Cobit method and focus on the PO and AI domains. The implementation of HRIS governance at the Nurul Fikri Integrated Islamic School has been carried out even though it is still not running optimally because it has reached the expected level of maturity. The maturity level of the HRIS governance at the Nurul Fikri Integrated Islamic School is at level 2 (Managed Process) for both the PO and AI domains.